Assessment of the Parametric Reliability of the Side Surface of the Diesel Engine Piston during Its Design - Linkov, O.; Marchenko, A.; Pylyov, V. V.; Lykov, S. (Kaunas University of Technology, 2023)
Scientific and technical works aimed at improving the complex range of requirements for environmental friendliness and efficiency of diesel engines while maintaining the trend of increasing their specific power are highly relevant nowadays. Proposed solutions often lead to an increase in the thermal stress of the combustion chamber parts, the piston in particular. At the same time, cases of loss of reliability of the side surface of the piston due to an unforeseeable reduction of the clearance in the piston and cylinder liner pair are noticed at the stage of experimental research. The creep limits for two piston aluminium alloys are studied in the article. The thermal stress of pistons of two designs at different diesel loads is examined. The influence of the piston material creep on the loss of parametric reliability of the designs is shown.
Keywords: diesel engine piston; side surface of the piston; thermal stress; material creep; creep limit; parametric reliability